Critique in the neoliberal age - Johnson, Pauline, 1953- (Abingdon, Oxon ; New York, NY : Routledge, 2020)
"Critique in a Neoliberal Age brings a critique of ideology to main debates within economic sociology, populism studies, the neoliberal university, therapy culture, contemporary intimacies and feminism"--
OCLC-licensed vendor bibliographic record.
Keywords: Sociology -- Research; Neoliberalism; SOCIAL SCIENCE / Sociology / General